Republic of Congo : Interim Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report ;, 2005)
This paper examines Congo's Interim Poverty Reduction Strategy Paper (I-PRSP). Congo's I-PRSP explains the features and causes of poverty in Congo. It provides a short- and medium-term vision of development as well as a strategic orientation for a return to sustainable and equitable growth. The main objective is steady poverty reduction. The choice and implementation of strategic orientations and priority actions in the I-PRSP are consistent with the government's commitment to rebuilding the economy and in line with the Millennium Development Goals, the New Partnership for Development, and the government's 'nouvelle esperance' program.